The Effect of Variations in HPMC and Carbopol Bases on The Physical Stability of Okra (Abelmoschus esculentus L.) Fruit Gel Formulations - Irman Idrus; Rahayu Apriyanti; Syaiful Katadi; Nurfitriyana Rahmat; Sabda Wahab; Dzul Asfi (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2023)
Okra fruit (Abelmoschus esculentus L.) is a vegetable that is often used as medicine. Okra fruit contains flavonoids which are antioxidants. Gel formulation with a concentration of 5%, and various combinations of HPMC and carbopol bases. This research aims to determine the physical stability of gel preparations and the effect of variations in the concentration of gelling ingredients in the preparations. The gel formulation consists of 4 formulas, namely F0, F1, F2, and F3. Physical stability tests include organoleptic tests (odor, color and texture), homogeneity, pH, spreadability, stickiness, viscosity and synergy. Tests were carried out for 14 days of storage, namely on days 1, 3, 5, 7, and 14 at room temperature (25℃). The observation results showed that in the organoleptic test there was no change in color, odor and texture in the gel preparation during 14 days of storage. The four gel formulas are homogeneous and there is no synergy. Variations in the combination of HPMC and carbopol bases affect the physical properties of the gel, including pH, viscosity, spreadability and adhesion. HPMC and Carbopol affect the pH of the preparation, the higher the Carbopol content and the lower the HPMC content, the more acidic it is. Carbopol and HPMC affect the values of spreadability, viscosity and adhesion because the higher the concentration of carbopol and HPMC produces a thick gel preparation so that the spreadability decreases, viscosity increases and adhesion also increases.